A cost-effective airborne multisensor system for pipeline monitoring using a quadcopter. (11th March 2023) - Benyeogor, Mbadiwe S.; Olatunbosun, Adeboye; Olakanmi, Oladayo O.; Lawal, Olusegun I.
Recently, there has been a high demand for unmanned aerial vehicles (UAVs) for oil and gas pipeline inspection. Therefore, a multisensory quadcopter is developed using an edge controller to meet this demand. In addition, a pair of thermosensitive gas sensors and nondispersive infrared (NDIR) gas sensors are embedded in the quadcopter for detecting pipeline leakages. Python scripts are used to analyse the quadcopter's dynamics during flight in order to evaluate its ability to deploy instruments. The result of this work is a system that can fly semi-autonomously to survey pipeline infrastructure in real-time. Performance analysis has been carried out on the system and its subcomponents. Results reveal that the developed system functions as predicted. Moreover, we envisage that this system will help improve safety, situational awareness, and decision-making in the oil and gas industries.